Pertumbuhan dan hasil tanaman kacang hijau (Vigna radiata L.) pada berbagai agents dan dosis pupuk hayati - Azamudin Tifani, Aaz; Miftah Dieni Sukmasari (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2024)
This study aimed to analyze the interaction between Mycogrow and Bionsecta formulas and green beans' growth and yield (Vigna radiata L.). The research method uses a field experiment method with a group randomized design factorial arrangement consisting of two factors repeated four times. The first factor,  Mycogrow (m) formulas, consists of 3 levels: m1 = 5 g/plant, m2 = 10 g/plant, and m3 = 15 g/plant. Meanwhile, the second factor, Bionsecta (b) formulas, consists of 3 levels: b1 = 5 g/plant, b2 = 10 g/plant, and b3 = 15 g/plant. The data obtained is analyzed statistically with the f-test (Multivariate Analysis of Varians), and the average value of each treatment is determined using the Duncan Multiple Range Test (DMRT). The results showed an interaction between the m and b formulas. The best interaction was shown in the m2b2 combination: moycogrow 10 g and bionsects 10 g. The dose treatment of the Mycogrow formula (10 g/plant) is the best treatment on the number of leaves, age four wap, root length, number of pods per plant, and seed weight per plant. On the independent effect of giving bionsecta, a dose of 10 grams showed the best results on the number of pods per plant and seed weight per plant.